Den hulde. Om kildegrundlaget for Grundtvigs ungdomsforelskelse - Møller, Jes Fabricius (Historisk Tidsskrift, 2024)
The Fair One – Grundtvig’s Early Love The great Danish national poet, theologian, historian and much more N.F.S. Grundtvig’s period as a tutor at Egeløkke Manor on the island of Langeland from 1805 to 1808 was significant because it opened his eyes to the Jena Romantics. Though his Romantic phase lasted only a couple of years, influence from German philosophers runs as an undercurrent through most of his writings. Grundtvig’s biographers have pointed to a love story as an explanation for this Romantic turn: He is supposed to have fallen in love with the lady of the manor, Constance Leth. Soon after his return to Copenhagen, Grundtvig wrote a letter to his friend, Christian Molbech, that „a fair one“ had opened his eyes. Molbech assumed the woman was Mrs. Leth, and, when correspondence between Grundtvig and Molbech was published in the 1880’s, this assumption was quickly regarded as an established fact. However, Grundtvig’s diaries reveal that before moving to Langeland, he had already met and fallen in love with his future wife, Lise Blicher. It is also clear that the years on Langeland were emotionally stressful and involved a woman who was not Lise. But he never identified that woman, nor did he describe their relationship in any detail. Grundtvig’s own description of his Romantic conversion in the above mentioned letter to Molbech is in fact rather generic, and certain elements indicate that the fair one could just as well have been Lise, with whom he had a loving relationship. Even though many scholars have pointed out that as an autobiographer, Grundtvig was more poet than historian, Grundtvig’s biographers have been eager to believe the classic story of a young man falling in love with an older, married woman of noble birth, because it is too good to remain untold. Correspondingly, Lise Blicher has generally been described as faithful and kind but also bland and insignificant, unlikely to be the object of the great Grundtvig’s true love or passion. On both accounts, the sources indicate a less exciting but possibly more reasonable story.